Tendências da desigualdade salarial para coortes de mulheres brancas e negras no Brasil - Oliveira, Ana Maria Hermeto Camilo de; Rios-Neto, Eduardo Luiz Gonçalves (Estudos Econômicos (São Paulo), 2006)
We analyze trends of wage inequality of the Brazilian female labor force, by race, during the 1980s and 1990s. Increasing returns to skills and increasing demand for skilled labor result in a divergence of wages growth between high and low skilled workers. This increasing gap results in an increase of wage inequality by race. In order to interpret trends, we take into account race differences in marriage patterns, fertility, household arrangements, educational levels, labor market participation, skill levels, occupational location and earnings, distinguishing between period and cohort measures. We use 1987-1999 Brazilian Household Sample Surveys data to examine the importance of within- and between-cohort changes for black and white women. Earnings functions are estimated from the pooled time-series of these cross-section data, using OLS and quantile regressions.